Elucidating the role of dsRNA sensing and Toll6 in antiviral responses of Culex quinquefasciatus cells - Brian C. Prince; Kalvin Chan; Claudia Rückert (Frontiers in Cellular and Infection Microbiology, 2023)
The first step of any immune response is the recognition of foreign molecular structures inside the host organism. An important molecule that is generally foreign to eukaryotic cells is long double-stranded RNA (dsRNA), which can be generated during virus replication. The mechanisms of sensing viral dsRNA are well-studied in mammalian systems but are only poorly understood in insects, including disease vectors such as Culex quinquefasciatus mosquitoes. These mosquitoes are vectors for important arboviruses, such as West Nile virus, and Culex species mosquitoes are distributed across the globe in many temperate and tropical regions. The major antiviral response triggered by dsRNA in mosquitoes is RNA interference – a sequence-specific response which targets complementary viral RNA for degradation. However, here, we aimed to identify whether sequence-independent dsRNA sensing, mimicked by poly(I:C), can elicit an antiviral response. We observed a significant reduction in replication of La Crosse virus (LACV) in Cx. quinquefasciatus mosquito cells following poly(I:C) priming. We identified a number of antimicrobial peptides and Toll receptors that were upregulated at the transcript level by poly(I:C) stimulation. Notably, Toll6 was upregulated and we determined that a knockdown of Toll6 expression resulted also in increased LACV replication. Future efforts require genetic tools to validate whether the observed Toll6 antiviral activity is indeed linked to dsRNA sensing. However, large-scale functional genomic and proteomic approaches are also required to determine which downstream responses are part of the poly(I:C) elicited antiviral response.